2003
DOI: 10.1016/s0735-1097(02)02696-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender, age, and heart failure with preserved left ventricular systolic function

Abstract: In elderly patients hospitalized with HF, preserved systolic function is primarily a condition of women, independent of important demographic and clinical characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
143
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(157 citation statements)
references
References 19 publications
10
143
1
3
Order By: Relevance
“…This percentage is similar to Masoudi et al's report of 35% in a chart review study of over 19,000 Medicare beneficiaries hospitalized who had been discharged with the principal diagnosis of heart failure [13]. Communitybased epidemiological studies have demonstrated that diastolic heart failure is common and is particularly prevalent in older patients, women, and those with a history of hypertension [9,13,14].…”
Section: Discussionsupporting
confidence: 84%
“…This percentage is similar to Masoudi et al's report of 35% in a chart review study of over 19,000 Medicare beneficiaries hospitalized who had been discharged with the principal diagnosis of heart failure [13]. Communitybased epidemiological studies have demonstrated that diastolic heart failure is common and is particularly prevalent in older patients, women, and those with a history of hypertension [9,13,14].…”
Section: Discussionsupporting
confidence: 84%
“…It has been reported to account for more than 50 % of all heart failure patients [4,5]. The prevalence of HFpEF increases with age [1,11,12] and is reported to be more common in women than in men [13][14][15][16]. In HFpEF, dyspnea due to pulmonary congestion is frequently the earliest symptom, whereas muscle fatigue is more prominentinheart failure with reduced EF owing to the reduced cardiac output, impairment of vasodilator capacity, and abnormalities of skeletal muscle metabolism [17].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to HF/low-EF, patients with HF/PEF are more likely to be elderly, and hypertensive, and less likely to have previous therapy with ACE inhibitors and ARBs [43] .…”
Section: Medical Therapy Of Hf/pefmentioning
confidence: 99%